NATURE’S WARRIORS: UNVEILING THE POWER OF ANTICANCER MEDICINAL PLANTS - Shubhangi Shelar1, Snehal Bagadane, Shrutika Gaikwad, Snehal Chakorkar1 (Chelonian Research Foundation, 2024)
Cancer is characterized by the unbridled multiplication of abnormal cells that can invade surrounding tissues and spread through lymphatic and vascular pathways. Though research has made leaps and bounds in recent years, the battle against cancer continues. Our arsenal against this enemy ranges from traditional methods like surgery, chemotherapy, and radiation therapy to cutting-edge advancements. However, these therapies often come at a cost, harming healthy cells as they target the cancerous ones. This is where medicinal plants emerge as potential allies. Many plants possess potent anticancer properties. They achieve this through various mechanisms, such as blocking harmful enzymes, activating protective ones, aiding DNA repair, and triggering antioxidant reactions. This review delves into the promising potential of naturally occurring compounds found in traditionally and currently used medicinal plants as weapons against cancer. The key lies in their inherent antioxidant capabilities, which form the cornerstone of their anticancer activity. Furthermore, the rich tapestry of pharmacological properties found in medicinal plants, including cytotoxicity and chemoprevention, has drawn significant attention to natural products like flavonoids, terpenoids, and steroids. This article explores the exciting promise of harnessing these naturally occurring chemicals from medicinal plants to combat cancer effectively. Keywords: Phytopharmaceuticals, Anticancer property, Chemotherapy, Herbal plants, Cancer